2011
DOI: 10.1146/annurev-physiol-012110-142145
|View full text |Cite
|
Sign up to set email alerts
|

Heart Valve Structure and Function in Development and Disease

Abstract: The mature heart valves are made up of highly organized extracellular matrix (ECM) and valve interstitial cells (VIC) surrounded by an endothelial cell layer. The ECM of the valves is stratified into elastin-, proteoglycan- and collagen-rich layers that confer distinct biomechanical properties to the leaflets and supporting structures. Signaling pathways have critical functions in primary valvulogenesis as well as maintenance of valve structure and function over time. Animal models provide powerful tools to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
436
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 406 publications
(450 citation statements)
references
References 109 publications
12
436
1
1
Order By: Relevance
“…Remodeling of valvular interstitial cells and extracellular matrix, mainly collagens, proteoglycans, and elastin, is essential for maturation of the semilunar valves (61). Hdac3…”
Section: P-t)mentioning
confidence: 99%
“…Remodeling of valvular interstitial cells and extracellular matrix, mainly collagens, proteoglycans, and elastin, is essential for maturation of the semilunar valves (61). Hdac3…”
Section: P-t)mentioning
confidence: 99%
“…Wnt/β-catenin signaling also is active during endocardial cushion maturation, but the specific role for this pathway in valve lineage differentiation is yet to be determined [10]. Valve development continues with the remodeling of the endocardial cushions into thin elongated leaflets composed of stratified ECM, which occurs soon after birth in mice and humans [2]. The ECM layers consist of the collagen-rich fibrosa, proteoglycan-rich spongiosa, and elastin-rich atrialis/ ventricularis [2].…”
Section: Heart Valve Developmentmentioning
confidence: 99%
“…Valve development continues with the remodeling of the endocardial cushions into thin elongated leaflets composed of stratified ECM, which occurs soon after birth in mice and humans [2]. The ECM layers consist of the collagen-rich fibrosa, proteoglycan-rich spongiosa, and elastin-rich atrialis/ ventricularis [2]. These layers are oriented in the semilunar and AV valves with the elastin layer adjacent to blood flow.…”
Section: Heart Valve Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…4,77 The aortic valve leaflet is known to exhibit a complex tri-layer striation with ECM components, mainly GAGs, collagen, and elastin. 77 We thus quantitatively evaluated and compared the secretion and remodeling of these ECM components. We observed that all these three cell types were able to dynamically produce and remodel their own matrix within the hydrogels.…”
mentioning
confidence: 99%